The role for medical thoracoscopy in pneumothorax - Parrish, Scott; Browning, Robert F.; Turner Jr., J. Francis; Zarogoulidis, Konstantinos; Kougioumtzi, Ioanna; Dryllis, Georgios; Kioumis, Ioannis; Pitsiou, Georgia; Machairiotis, Nikolaos; Katsikogiannis, Nikolaos; Tsiouda, Theodora; Madesis, Athanasios; et al. (Journal of Thoracic Disease; Vol 6, Supplement 4 (October 10, 2014): Journal of Thoracic Disease (Pneumothorax: From Definition to Diagnosis and Treatment), 2014)
Pneumothorax is a life threatening situation that requires fast treatment. There are two major classifications: Primary and Secondary. Staging of pneumothorax is also very important for treatment. Treatment of pneumont can be performed either from thoracic surgeons, or pulmonary physicians. In our current work we provide up-to-date information regarding pneumothorax classification, staging and treatment from the point of view of expert pulmonary physicians.